Балансово-оптимізаційна модель визначення обсягів власного видобутку вугілля та його імпортування з урахуванням впливу заходів з модернізації та реконструкції на техніко-економічні показники функціонування вуглевидобувних підприємств - Bilan T.R. (General Energy Institute of the National Academy of Sciences of Ukraine, 2017)
We have developed the structure of a balance-optimization model for determining the volumes of coal production and import with regard for the increase in industry's competitiveness by reducing the prime cost of coal mining at state-owned enterprises after carrying out their reconstruction and modernization. The developed model takes into account the simultaneous consumption of separate coal grades under conditions of the limited possibilities of domestic coal mining and limited capacity of Ukrainian seaports. The implementations of balance of the supply and consumption of coal products is carried out through its import.